Does coenzyme Q10 supplementation help reduce statin‐induced myalgia?. Issue 3 (March 2015) - Over, Darrell R.; Durairaj, Vikram
Abstract : Evidence‐Based Answer : Currently evidence suggests that coenzyme Q10 (CoQ10) is probably not effective for statin‐related myalgia (SOR: C, heterogeneous RCTs).